Expectations of patients to nursing Staff during the hospitalization - Rabiasz, Renata; Makowicz, Dawid; Makowicz, Natalia (Nursing in the 21st Century, 2018)
EXPECTATIONS OF PATIENTS TO NURSING STAFF DURING THE HOSPITALIZATIONIntroduction. Due to the increasing incidence of a number of different diseases of Polish society , there is also a growing need for professional nursing care to be able to objectively assess how it should be expected to find out what the patients’ expectations are in this situation.Aim. The study aimed to define the main patient expectations for nursing staff during hospitalization. The purpose of the work was also to get to know the public opinion about the model of a modern nurse.Material and methods. The study was carried out on 200 patients hospitalized at various hospitals in Krosno, Strzyżów and Jasło at the end of January and February 2017. The method of the diagnostic survey was used with the questionnaire survey, which consisted of 10 closed questions.Results. For 87% of patients the most important care is caring care, 79.5% of the respondents require good practice. For 66% of respondents it is important to provide information on their questions, while 51.5% of people are important to enable contact with family. The overwhelming majority, (95%) of respondents stress the importance of possible assistance rather than helping them in their everyday life in the ward. 72.5% of patients assess the nurse-patient relationship very well.Conclusions. For patients a very important element of hospitalization is caring nursing care. Hospitalized people are much more likely to appreciate the professional experience of nursing staff than achieved by them academic titles. The profession of a nurse/nurse is perceived by patients as a separate profession. Patients appreciate the smile and nice attitude of the nursing staff.